Performance of diversity combining ARQ error control in a TDMA SC-FDE system - Pereira, Miguel (2018)
The Quality of Service (QoS) requirements for modern broadband wireless systems can be very high, with small error rates and delays. Packets with errors are usually discarded and need to be retransmitted, leading to performance degradation. An alternative to simple retransmissions like Automatic Repeat reQuest (ARQ) schemes, that can minimize the degradation is to combine the signals associated to different transmission attempts, usually called diversity combining techniques. This paper considers the use of Single-Carrier (SC) modulations with Frequency-Domain Equalization (FDE) and low-complexity soft combining ARQ schemes. The time diversity combining technique presented in this paper, allows packets associated to different transmission attempts to be combined in a soft way so as to improve the performance. This technique is employed in a Time Division Multiple Access (TDMA) scheme. An accurate analytical model is proposed for the evaluation of the uplink packet delay in non-saturated traffic condition, and for the system's throughput (goodput) considering a generic packet arrival process. Physical (PHY) layer (packet error rates) and system-level (goodput and packet delay considering both PHY and Medium Access Control (MAC) layers) results are presented and validated by simulations for two distinctive arrival processes: Poisson and Geometric